Pertanggungjawaban Pidana Terhadap Pelaku Produksi, Distribusi, dan Penjualan Set Top Box Ilegal yang menimbulkan Kerugian Konsumen di Indonesia - Putri Amelia Anugraini; Abraham Ferry Rosando (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The transition from analog to digital broadcasting in Indonesia has increased the public’s need for Set Top Boxes (STBs). However, this process has also raised legal concerns due to the widespread circulation of illegal STBs that fail to meet technical standards and certification requirements. This study analyzes the criminal elements involved in the distribution of illegal STBs and examines the criminal liability of business actors engaged in their production, distribution, or sale. The research employs a normative legal method using statutory and conceptual approaches. Findings indicate that the circulation of illegal STBs fulfills both actus reus and mens rea under the Telecommunications Law, Consumer Protection Law, and the Electronic Information and Transactions Law. Business actors knowingly trade uncertified devices and disseminate misleading information through digital platforms, posing safety risks, harming the electronics industry, and obstructing the digital broadcasting migration program. The study concludes that addressing illegal STB distribution requires stronger law enforcement, enhanced regulatory oversight, updated digital trade regulations, and improved consumer literacy to ensure a safe and equitable digital broadcasting ecosystem..